2015
DOI: 10.1097/coc.0b013e3182a1b448
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Outcomes in Patients With Carcinoma of the Cervix Treated With Concurrent Radiation and Cisplatin Versus Cisplatin/5-FU Compared With Radiation Alone

Abstract: Cisplatin-based concurrent chemoradiotherapy showed a trend toward improved recurrence-free survival survival in the definitive treatment of nonmetastatic cervical cancer. The addition of 5-FU to cisplatin did not appear to significantly impact survival or recurrence-free survival. Adenosquamous histology was associated with a higher risk of recurrence as compared with other histologic subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…This study included 17 literature with 4,106 patients, while the literature consisted of 5 retrospective studies [ 10 14 ] and 12 prospective studies [ 4 , 8 , 15 24 ]. Among them, 2,066 patients received platinum-based dual drug therapy combining CCRT, while 2,040 patients received platinum monotherapy combining CCRT.…”
Section: Resultsmentioning
confidence: 99%
“…This study included 17 literature with 4,106 patients, while the literature consisted of 5 retrospective studies [ 10 14 ] and 12 prospective studies [ 4 , 8 , 15 24 ]. Among them, 2,066 patients received platinum-based dual drug therapy combining CCRT, while 2,040 patients received platinum monotherapy combining CCRT.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some of the most powerful predictors of patient outcomes are not particular laboratory values but comprehensive and integrative assessments such as the performance status, a measure of a patient's overall well-being through combined quantitative (test values) and qualitative observations (physical examination). 16…”
Section: Clinical Judgment: the Original Similarity-based Approachmentioning
confidence: 99%
“…3,4 According to various studies, Capecitabine has shown promising results as a radio sensitizer in squamous cell carcinoma of cervix. 7 Factors like broad clinical effectiveness and low toxicity profile among different malignancies advocates its use in cervical tumors treatment. Capecitabine is an oral 5-FU pro-drug; it is converted to 5-FU by enzyme thymidine phosphorylase (TP).…”
Section: Introductionmentioning
confidence: 99%